Hubungan Karakteristik Ibu Dan Pola Asuh Gizi Dengan Kejadian Balita Stunted di Desa Hargorejo Kulon Progo DIY - Astuti, Dian Kusuma; , Dwi Sarbini, SST; , Luluk Ria Rakhma, S.Gz., M.Gizi (2016)
Stunted is a long linear growth based on the index of weight for age (PB/U)< -2SD. Stunted has an impact on the decrease of functional capacity. Factors that affect stunted growth include maternal height , arm circumference of mother during pregnancy , maternal age and nutrition care pattern. To assess the correlations between characteristics of mother and nutrition care pattern and the incidence of stunted on toddlers at Hargorejo Kulon Progo , Yogyakarta. This study was quantitative research with cross-sectional design. The respondents were 47 and selected through systematic random sampling technique. Data maternal characteristics and nutritional care pattern were obtained through interviews. Analysis of data using Pearson product moment statistical tests and Spearman rank. Most of children under five who are stunted 68.2 % had mothers with short height. Mothers with chronic energy malnutrition during pregnancy had 47.6%. Children under five who are stunted 50% of mother with age < 21 years old or > 30 years had stunted children. Most of the nutrition care pattern of mothers was average which was 78.9 % had stunted children. There was a correlations between height of mothers and stunted (p = 0.040 ). There was no correlations between the circumference during pregnancy and stunted (p=0.922). There was no correlation between maternal age and the incidence of stunted ( p = 0.635 ). There was a correlations between nutrition care pattern with stunted ( p = 0.000 ).